E-MODULES FOR CARGO MANAGEMENT COURSES - Alfian Deva Yusriyanto, Mokhammad; Silk Moonlight, Lady; Fatmawati, Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aviation Polytechnic of Surabaya is a vocational education institution that organizes training in the aviation industry. One of the competencies of this educational institution is commodity management. In the Air Transportation Management Study Program lectures, there is a Freight Forwarding course. With the convenience of internet access, theSurabaya Aviation Polytechnic needs to provide interesting and effective learning media as a teaching tool for cadets and participants of the D3 Air Transportation Management degree program at the Surabaya Aviation Polytechnic. Thepurpose of this development study is to find out the process of development, feasibility and response to the learning environment based on electronic modules for cadets and lecturers in the Cargo Management Department of Air Transportation Management Diploma 3 study program and to produce learning media in the form of e-Module in the form of videos using Canva for the preparation of material and uploaded via Learning Management System (LMS) Surabaya Aviation Polytechnic. By using ADDIE Model with five stages of development Analysis, Design, Development, Implementation, Evaluation. This study uses a questionnaire with the media Google Form which is testedusing Likert scale. From the results of the Air Transportation Management Cadets response test regarding e-Module Cargo Management reaches 83.55% in the very good category and can be used to help cadets and training participants learn. Validation results stated e-Module Management Cargo from instructors or media experts get 90.63% in a very good category for further use.